2022
DOI: 10.53353/atrss.1079035
|View full text |Cite
|
Sign up to set email alerts
|

Duygusal Emeğin İşten Ayrılma Niyetine Etkisinde Örgütsel Bağlılığın Aracılık Rolü: Yiyecek İçecek İşletmeleri Üzerinde Bir Araştırma

Abstract: işletmelerinin 312 çalışanı üzerinde yapılmıştır. Önceki araştırmalardan farklı olarak değişkenlerin alt boyutları da analizlere dahil edilmiştir. Verilerin analiz edilmesinde SPSS ve Process v4.0 yazılımı kullanılmıştır. Analiz sonuçlarına göre duygusal emeğin yüzeysel ve samimi davranış boyutlarının işten ayrılma niyetine etkisinde örgütsel bağlılığın aracılık etkisi bulunmaktadır. Ancak duygusal emeğin derin davranış boyutunun işten ayrılma niyetine etkisinde örgütsel bağlılığın herhangi bir aracılık rolü t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…As a result of the research conducted on employees working in food businesses between November 2021 and January 2022, it has been shown that organizational commitment is important for food and beverage businesses. Organizational commitment has a mediating effect in the influence of emotional labour on intention to leave job (Polat, 2022). Emotional labour causes stress on employees and increases their intention to leave.…”
Section: The Intention To Leave Jobmentioning
confidence: 99%
“…As a result of the research conducted on employees working in food businesses between November 2021 and January 2022, it has been shown that organizational commitment is important for food and beverage businesses. Organizational commitment has a mediating effect in the influence of emotional labour on intention to leave job (Polat, 2022). Emotional labour causes stress on employees and increases their intention to leave.…”
Section: The Intention To Leave Jobmentioning
confidence: 99%